May measurement month 2018: an analysis of blood pressure screening results from Colombia (2020)
High blood pressure (BP) is the leading global preventable cause of death and the most common risk factor for cardiovascular disease (CVD). However, due to its asymptomatic nature, the lack of awareness of this condition causes underdiagnosis and low rates of adherence to pharmacological treatment. Looking for practical approaches to increase awareness worldwide, the International Society of Hypertension (ISH) implemented the 2nd May Measurement Month campaign in 2018 (MMM18). In order to contribute to this initiative, Colombia participated as one of the 89 countries involved in this hypertension screening programme. Blood pressure was measured in subjects from 11 departments in Colombia. Under the leadership of the Fundacio´n Oftalmolo´gica de Santander (FOSCAL), 400 volunteers across the country collected the data following the MMM protocol. Measurements from 35 548 participants with a mean age of 41.9 years were obtained. In total, 9475 (26.7%) of the total population studied had hypertension. Of those with hypertension, 69.9% of these subjects were aware of their condition, 65.0% were on antihypertensive medication, and 43.1% had controlled BP. Of those on medication, 66.3% had controlled BP. Hypertension screening, awareness, treatment, and control should be a priority in public health objectives due to its elevated burden of disease and direct association with increased CVD. The MMM campaign provided a positive impact in the diagnosis of hypertension across Colombia. Although efforts are being made to expand treatment capability and adherence, still more are needed to insure a broader coverage of antihypertensive medication in Colombia.